2010
DOI: 10.1007/s10592-010-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure of blue whales (Balaenoptera musculus) in Australian feeding aggregations

Abstract: The worldwide distribution of blue whales (Balaenoptera musculus) has not prevented this species from becoming endangered due to twentieth century whaling. In Australia there are two known feeding aggregations of blue whales, which most likely are the pygmy subspecies (B. m. brevicauda). It is unknown whether individuals from these feeding aggregations belong to one breeding stock, or multiple breeding stocks that either share or occupy separate feeding grounds. This was investigated using ten microsatellite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…The lack of a clear population structure for the whole data set found in this study agrees with the lack of structure found in blue whales of the southern hemisphere [28]. It also agrees with the results on bioacoustic studies that suggest the presence of a single population in the Northeast Pacific, extending from Vancouver to the Dome of Costa Rica, and possibly beyond Ecuador [22], [23].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The lack of a clear population structure for the whole data set found in this study agrees with the lack of structure found in blue whales of the southern hemisphere [28]. It also agrees with the results on bioacoustic studies that suggest the presence of a single population in the Northeast Pacific, extending from Vancouver to the Dome of Costa Rica, and possibly beyond Ecuador [22], [23].…”
Section: Discussionsupporting
confidence: 91%
“…The mean observed heterozygosity of blue whales in the GC (H O  = 0.74) was similar to values reported for this species in the South Pacific (Ho = 0.72) and the Antarctic (Ho = 0.75) Oceans [27], and higher than those found in Australian aggregations (H O  = 0.66 in Perth Canyon, Western Australia; Ho = 0.59 in Bonney Upwelling, Southern Australia) [28]. Despite the smaller estimated blue whale population size in the GC (n = 283, %CV = 48.4) [26], the observed diversity and the inbreeding coefficient (F IS close to zero) suggest a panmictic population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The third population off Australia and Indonesia moves along the western and southern coasts of Australia in spring/summer [30], [31], before likely migrating to Indonesia in winter for breeding [3]. Recent genetic studies suggest that all pygmy blue whales seen around Australia are likely to belong to the same breeding stock [32]. Acoustic recordings also support longitudinal movements from east to west in the sub-Antarctic latitudes of the Indian Ocean [16].…”
Section: Introductionmentioning
confidence: 99%
“…Five individuals sampled off Australia had known resamples (Attard et al . ; only two were inter‐seasonal resamples) that were not included within the above sample size. Samples were preserved in either 20% DMSO saturated with NaCl or 70–100% ethanol.…”
Section: Methodsmentioning
confidence: 99%